MIX CODES, INTERFERENCE, ON THE USE OF ARABIC EXPRESSIONS ON SOCIAL MEDIA: A PHENOMENOLOGICAL STUDY ON SOCIAL MEDIA WHATSAPP, lINE, FACEBOOK, INSTAGRAM, AND TWITTER. - Firdaus, Mochammad; Fadhlan, Muhammad; Ibrahim, Faisal Mahmoud Adam; Rais, Ahmad (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
Code interference and Interference are serious problems for language activists in conveying messages on social media. This study aims to 1) analyze linguistic phenomena based on interference elements and mix codes in Arabic expressions used on social media. This research is qualitative research with a phenomenological approach. Data was collected by the listening method assisted by advanced techniques such as recording. The design of collecting data in this study uses observation techniques. The type of data collected in the form of Arabic expressions on social media WhatsApp, Instagram, line, and Facebook is described in full to conclude the use of Arabic expressions on social media WhatsApp, line, Facebook, and Instagram. At the same time, the data analysis technique in this study uses the Miles Huberman and Saldana methods, which include four things: Collecting data, Condeniasai data, Data Reduction, and Giving Data Conclusions. The findings of this study include several items, namely: 1) Indonesian Interference with Arabic expressions on social media consists of semantic, syntactic, morphological, lexicology, and phonological Interference; 2) factors that cause Interference in the use of Arabic expressions include Indonesian dominance, lack of Arabic vocabulary, and Indonesian habits are so inherent that they are difficult to abandon